Yoga Improves Quality of Life among Breast Cancer Patients - Henri Setiawan; Heri Ariyanto; Reffi Nantia Khaerunnisa; Fidya Anisa Firdaus; Ade Fitriani (Faletehan Health Journal, 2021)
Yoga was a therapy that combined breathing, relaxation and meditation techniques and stretching exercises. The benefits of yoga in general could increase strength, flexibility, train balance, reduce pain, train breathing, smooth organ function, inner calm and improve quality of life. Several differences in the results of studies can influence the decisions of patients and health providers in planning appropriate interventions for breast cancer patients. This literature review aimed to explain the effectiveness of yoga on the quality of life of patients with breast cancer. The research data were identified from five journal databases including PubMed, JSTOR, Willey Online Library, Sage Journal and Taylor Francis Online by using the PIOS (Participant, Intervention, Outcomes and Study Design) method and MeSH term on the advanced search engine. Articles that became research data were articles published in 2007 to 2020 in the English version, open access and full text in the form of original articles or research articles. Of the 1,645 articles found, a screening process was carried out using PRISMA flowchart to eliminate articles that did not meet the criteria. In this literature review study, 9 articles were found that prove that the use of yoga interventions could improve the quality of life of patients. This study reinforced the findings of previous research which showed that yoga could be used effectively in the process of treating patients with breast cancer.